Loss of Angiotensin‐Converting Enzyme 2 Exacerbates Diabetic Retinopathy by Promoting Bone Marrow Dysfunction. (15th July 2018) - Duan, Yaqian; Beli, Eleni; Li Calzi, Sergio; Quigley, Judith L.; Miller, Rehae C.; Moldovan, Leni; Feng, Dongni; Salazar, Tatiana E.; Hazra, Sugata; Al‐Sabah, Jude; Chalam, Kakarla V.; Phuong Trinh, Thao Le; et al.
Abstract: Angiotensin‐converting enzyme 2 (ACE2) is the primary enzyme of the vasoprotective axis of the renin angiotensin system (RAS). We tested the hypothesis that loss of ACE2 would exacerbate diabetic retinopathy by promoting bone marrow dysfunction. ACE2 –/y were crossed with Akita mice, a model of type 1 diabetes. When comparing the bone marrow of the ACE2 –/y ‐Akita mice to that of Akita mice, we observed a reduction of both short‐term and long‐term repopulating hematopoietic stem cells, a shift of hematopoiesis toward myelopoiesis, and an impairment of lineage – c‐kit + hematopoietic stem/progenitor cell (HS/PC) migration and proliferation. Migratory and proliferative dysfunction of these cells was corrected by exposure to angiotensin‐1‐7 (Ang‐1‐7), the protective peptide generated by ACE2. Over the duration of diabetes examined, ACE2 deficiency led to progressive reduction in electrical responses assessed by electroretinography and to increases in neural infarcts observed by fundus photography. Compared with Akita mice, ACE2 –/y ‐Akita at 9‐months of diabetes showed an increased number of acellular capillaries indicative of more severe diabetic retinopathy. In diabetic and control human subjects, CD34 + cells, a key bone marrow HS/PC population, were assessed for changes in mRNA levels for MAS, the receptor for Ang‐1‐7. Levels were highest in CD34 + cells from diabetics without retinopathy. Higher serum Ang‐1‐7 levels predicted protection from development of retinopathy in diabetics. Treatment with Ang‐1‐7 or alamandine restored the impaired migration function of CD34 + cells from subjects with retinopathy. These data support that activation of the protective RAS within HS/PCs may represents a therapeutic strategy for prevention of diabetic retinopathy. Stem Cells 2018;36:1430–1440 Abstract : Hematopoietic stem/progenitor cells (HS/PC) are important for vascular repair. This study showed that ACE2 deficiency exacerbates diabetes‐induced dysfunction of HS/PCs in bone marrow and promotes the development of diabetic retinopathy in both murine model and in humans. Two downstream peptides of ACE2, Ang‐(1‐7) and alamandine, improve diabetic HS/PC functions and may serve as novel therapeutic targets for prevention of diabetic retinopathy.